THE EFFECT OF INTERMITTENT FASTING ON SLEEP QUALITY AMONG MEDICAL STUDENTS AT DIPONEGORO UNIVERSITY - Nursabrina Marsya Safiqah Amansyah; Yuswo Supatmo; Hardian Hardian; Martha Ardiaria (Jurnal Kedokteran Diponegoro (Diponegoro Medical Journal), 2025)
Background: Intermittent Fasting (IF) is a type of fasting where a person alternates between fasting and eating within specific time intervals. Medical students tend to have poorer sleep quality compared to students from other faculties. This can negatively affect their academic performance, as well as their physical and mental health. While intermittent fasting is known to offer various health benefits, its effect on sleep quality in medical students has not been widely studied. Therefore, further research is needed to explore the impact of intermittent fasting on sleep quality among medical students. Objective: To determine the effect of intermittent fasting on the sleep quality of medical students. Methods: This study employed a quasi-experimental design with a one-group pretest-posttest design. The sample consisted of 24 medical students from the Faculty of Medicine, Diponegoro University, Semarang. The sample was selected using purposive sampling based on predetermined criteria. In this study, the intervention involved intermittent fasting using the 12:12 Time Restricted Feeding method. Fasting started from 6 PM to 6 AM on Mondays, Wednesdays, and Fridays for three consecutive weeks. Data analysis on sleep quality before and after the intervention was conducted using the Paired Sample T-Test. The correlation between confounding variables, such as stress levels and physical activity levels, and sleep quality was analyzed using Spearman's correlation test. Results: There was a significant decrease in the global PSQI score after the participants underwent intermittent fasting compared to before, with a p-value < 0.05 (p = 0.05 (p = 0.493). Conclusion: Intermittent fasting can improve the sleep quality of medical students.